The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1371/journal.ppat.1010075
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Mycobacterium bovis transmission between cattle and badgers using isolates from the Randomised Badger Culling Trial

Abstract: Mycobacterium bovis (M. bovis) is a causative agent of bovine tuberculosis, a significant source of morbidity and mortality in the global cattle industry. The Randomised Badger Culling Trial was a field experiment carried out between 1998 and 2005 in the South West of England. As part of this trial, M. bovis isolates were collected from contemporaneous and overlapping populations of badgers and cattle within ten defined trial areas. We combined whole genome sequences from 1,442 isolates with location and cattl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 72 publications
7
29
0
Order By: Relevance
“…Between-host transmission has been difficult to demonstrate and quantify. Recent phylodynamic studies by Crispell et al (2019) and van Tonder et al (2021), using M. bovis genomes from Woodchester Park and the Randomized Badger Culling Trial (RBCT) in GB, respectively, demonstrated inter-species transmission events were rare compared to intra-species ones (i.e. cattle-to-cattle transmission).…”
Section: Introductionmentioning
confidence: 99%
“…Between-host transmission has been difficult to demonstrate and quantify. Recent phylodynamic studies by Crispell et al (2019) and van Tonder et al (2021), using M. bovis genomes from Woodchester Park and the Randomized Badger Culling Trial (RBCT) in GB, respectively, demonstrated inter-species transmission events were rare compared to intra-species ones (i.e. cattle-to-cattle transmission).…”
Section: Introductionmentioning
confidence: 99%
“…Although the epidemiological units are different, the CB/BC ratios we obtained can be qualitatively compared with those obtained in phylodynamic studies, which were > 1 in some studies [ 61 , 62 ], and < 1 in other [ 63 ]. In England, Tonder et al recently analyzed retrospectively 12 putative transmission clusters reported between 1999 and 2008, and found CB/BC ratios > 1 in four clusters, and < 1 in the eight other [ 64 ]. In our study area, Duault et al [ 65 ] found a CB/BC ratio < 1.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for these patterns cannot be inferred from these retrospective models, but we speculate that it may involve the disturbance of wildlife [ 48 ]. Badgers ( Meles meles ) and, to a lesser extent, deer species, are a known wildlife host of bTB and are involved in the epidemiology of infection in local cattle herds [ 26 , 32 , 36 , 49 ]. Disturbances, such as road building and badger culling, are known to affect the socio-spatial structure of badger populations and can lead to the increased movement of animals amongst social groups (e.g., [ 50 , 51 , 52 ]).…”
Section: Discussionmentioning
confidence: 99%